SEA MOSS FLOUR (E. cottonii) AS AN INGREDIENTS OF PASTA: THE ANALYSIS OF ORGANOLEPTIC, PROXIMATE AND ANTIOXIDANT - R. A. Islamy; P. Senas; W. Isroni; N. B. Mamat; Y. Kilawati (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This research aims to assess the impact of adding Elkhorn Sea Moss Flour as a fiber source on the organoleptic characteristics and nutritional value of pasta. The treatments used are C0 = 0% addition of Elkhorn Sea Moss Flour; C1 = 30% ; C2 = 50%; C3 = 70%. The study utilized a completely randomized design (CRD) with one factor, comprising four concentration treatments replicated three times. The results showed that the addition of Elkhorn Sea Moss Flour to pasta resulted in significant increases in protein content, fiber, and antioxidant activity. Pasta with 70% Elkhorn Sea Moss Flour addition showed the highest fiber content and moderately high antioxidant activity, making it a potential functional food product. However, as Elkhorn Sea Moss Flour increased, there was a decrease in organoleptic parameters such as aroma, texture, and taste. Elkhorn Sea Moss Flour has great potential as an additive in functional food products, enriching fiber and antioxidant content, but its use should be carefully considered to ensure good consumer acceptance.